PERSEPSI GURU TERHADAP PENGELOLAANSARANA PEMBELAJARAN DI SMA NEGERI 1 SUNGAI GERINGGING - RIKI SANJAYA (Universitas Negeri Padang, 2016)
The purpose of this research is to see information about the Teachers' Perceptionsof the Management ofLearning Tools in SMA Negeri 1 Sungai Geringging. The population are63 people.The sample were taken by usingsaturated samplingtechniques. The research’s instrument usedwas questionnairewhich used Likert scale. Data analyzed by using mean score and performance level. The result of this research are the showed that the Teachers' Perceptionsof the Management of Learning Tools in SMA Negeri 1 Sungai Geringging in good category.